1997
DOI: 10.1677/jme.0.0180077
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a human leptin receptor using a biologically active leptin immunoadhesin

Abstract: Leptin, the product of the ob gene, is a hormone secreted by fat cells which is primarily involved in the regulation of body weight. We have generated a leptin immunoadhesin (leptin-IgG) which was more potent than leptin alone at reducing body weight and food intake when injected into ob/ob mice. This molecule was used to identify high affinity binding sites on human embryonic 293 kidney cells and subsequently to isolate a cDNA encoding the leptin receptor from this cell line by expression cloning. This recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 17 publications
(29 reference statements)
2
65
0
2
Order By: Relevance
“…Under conditions of clamped glycaemia, 7 leptin increases insulin sensitivity in normal rats both under fasting conditions and in the presence of hyperinsulinaemia; these effects do not appear to be dependent on altered body weight. It is also important to notice that the leptin receptor or its splice variants have so far been identi®ed in many different tissues including skeletal muscle, 8 which may be a possible target site for leptin action. It was recently shown that leptin stimulates glucose transport and glycogen synthesis in C 2 C 12 myotubes, 9 in opposition to previous ®ndings that leptin impairs insulin signaling, that is, insulin receptor autophosphorylation and insulin-receptor substrate (IRS)-1 phosphorylation in rat-1 ®broblasts, NIH3T3 cells 10 and HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of clamped glycaemia, 7 leptin increases insulin sensitivity in normal rats both under fasting conditions and in the presence of hyperinsulinaemia; these effects do not appear to be dependent on altered body weight. It is also important to notice that the leptin receptor or its splice variants have so far been identi®ed in many different tissues including skeletal muscle, 8 which may be a possible target site for leptin action. It was recently shown that leptin stimulates glucose transport and glycogen synthesis in C 2 C 12 myotubes, 9 in opposition to previous ®ndings that leptin impairs insulin signaling, that is, insulin receptor autophosphorylation and insulin-receptor substrate (IRS)-1 phosphorylation in rat-1 ®broblasts, NIH3T3 cells 10 and HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the expression pattern of the two forms (long and short) of leptin receptors by Northern blot, in situ hybridization and quantitative PCR showed that the receptors are expressed in most tissues (brain, testes, ovary, kidney, spleen, intestines, brown and white adipose tissues, heart, lung, liver, skeletal muscle, and adrenals (14,18)), with the long form being prevalent in the hypothalamus (18), in addition to also being found in the medulla of the adrenal, the inner zone of the medulla of the kidney (16,18), pancreatic islets (19), and fat tissue (18).…”
Section: The Leptin Receptormentioning
confidence: 99%
“…Skeletal muscle and adipose tissue are the most important sites of postprandial glucose disposal, and in these tissues the stimulation of glucose uptake, glycogen synthesis and lipid synthesis are the main effects of insulin. The leptin receptor has been identified in muscle and in adipose tissue (14,18), a fact that makes these tissues possible target sites for the action of leptin.…”
Section: Leptin and The Insulin-sensitive Tissuesmentioning
confidence: 99%
See 2 more Smart Citations